Access to and Utilization of Endocrine Therapy Among Breast Cancer Survivors in Botswana - James R. Wester; Rachel B. Wagner; Bosa Motladiile; Isaac Nkele; Nkhabe Chinyepi; Moeketsi J. Makhema; Tara M. Friebel-Klingner; Peter Vuylsteke; Shahin Lockman; Scott Dryden-Peterson; Racquel E. Kohler (JCO Global Oncology)
PURPOSEBreast cancer (BC) is the most common female cancer worldwide, and the burden is increasing across sub-Saharan Africa. For women with hormone receptor–positive (HR+) cancers, endocrine therapy (ET) taken for 5-10 years can reduce the risk of recurrence by half. We explored experiences with ET and barriers to utilization among survivors in Botswana.METHODSWe recruited women with nonmetastatic disease from a survivorship cohort who had undergone mastectomy within 1-5 years for semi-structured interviews to explore experiences with treatment. This thematic content analysis focused on ET, so the sample included women with HR+ cancer who should have received ET and HR− women who reported taking ET.RESULTSWe analyzed interviews with 19 women (mean age 54 years, 42% stage I/II, 58% stage III). Three key themes were identified: (1) limited provider counseling, (2) challenges refilling prescriptions at public pharmacies, and (3) high medication and transportation costs associated with private pharmacies. Subthemes included immunohistochemistry result communication, lack of knowledge, frequent public pharmacy stockouts, inconvenient prescription refill policies, and medication switching and discontinuation, especially among participants with low socioeconomic positions (SEPs). Women's persistence, SEP, and financial support facilitated refills. Although some experienced side effects, they were not a common reason for discontinuation.CONCLUSIONBC survivors in Botswana face multilevel barriers to accessing and adhering to ET. Provider and health system improvements are needed to effectively communicate ET importance and increase access to consistently available and affordable medication.